2022
DOI: 10.1111/jcmm.17082
|View full text |Cite
|
Sign up to set email alerts
|

Adipose‐derived stem cell spheroids are superior to single‐cell suspensions to improve fat autograft long‐term survival

Abstract: Autologous fat transplantation is a widely used procedure for surgical reconstruction of tissues. The resorption rate of this transplantation remains high and unpredictable, reinforcing the need of adjuvant treatments that increase the long‐term stability of grafts. Adipose‐derived stem cells (ASC) introduced as single cells in fat has been shown clinically to reduce the resorption of fat grafts. On the other hand, the formulation of ASC into cell spheroids results in the enhancement of their regenerative pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…These include spinner flasks and bioreactors to increase “flow” in the culture system and microfluidics-based platforms for efficient nutrient diffusion, oxygenation, and waste metabolite disposal. It is also interesting to see the evolution of permeable membranes such as the Transwell ® (Merckmillipore, 0.4 µm) permeable supports and other semi-permeable membrane materials being integrated into perfusion systems and 3D bioprinting techniques to improve nourishment to the organoid during maturation [ 64 , 121 ]. These technologies have helped to increase the lifespan and utility of organoids to months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include spinner flasks and bioreactors to increase “flow” in the culture system and microfluidics-based platforms for efficient nutrient diffusion, oxygenation, and waste metabolite disposal. It is also interesting to see the evolution of permeable membranes such as the Transwell ® (Merckmillipore, 0.4 µm) permeable supports and other semi-permeable membrane materials being integrated into perfusion systems and 3D bioprinting techniques to improve nourishment to the organoid during maturation [ 64 , 121 ]. These technologies have helped to increase the lifespan and utility of organoids to months.…”
Section: Discussionmentioning
confidence: 99%
“…The method was used to generate and cultivate ovarian cancer spheroids using the OVCAR-8 cell line, resulting in spheroids that mimic the structure and cellular distribution of solid tumors. Microwell-based methods are limited by the fact that cells are clustered and cultured in a submerged medium, which can limit oxygen diffusion and lead to hypoxia and cell death, making it difficult to maintain high cell viability [ 117 , 121 ].…”
Section: Methods For the Generation And Culture Of Cancer Spheroids A...mentioning
confidence: 99%
“…However, the latter route of administration is not optimal because it relies on multiple and painful injection sites that cannot be adequately controlled spatially. A few studies showed that clusterization into spheroids enhanced the therapeutic effects of ASC, 36 , 37 fostering wound closure and increasing their engraftment with less cell apoptosis. Some authors introduced ASC spheroids on adhesive films directly covering the ulcer.…”
Section: Mechanism Of Action and Asc Delivery On Woundsmentioning
confidence: 99%
“…On the other hand, 3D cell cultures are much more effective in closely mimicking the heterogeneity and complexity of the tumor mass, and therefore are more predictive for in vivo results than conventional 2D cell cultures. 115 On these bases, we tested the activity of the newly developed complexes on spheroids obtained from human HCT-15 tumor cells. HCT15 cells are known for their ability to form spheroids, which makes them a valuable tool for studying the interactions between cancer cells and the surrounding microenvironment.…”
Section: Resultsmentioning
confidence: 99%